Comparative Analysis of Health and Sociodemographic Status of Working and Non-Working Women and Their Children: Health and Sociodemographic Status of Working and Non-Working Women - Akram, Shehla Javed; Zakir, Rubeena; Akram, Javed; Liaqat, Rameesa; Mujahid, Fizzah; Syed, Sana; Liaqat, Fizza; Saeed, Anam; Khurram, Hafiza Manahil (Pakistan Journal of Health Sciences, 2024)
Women have responsibilities of home management and raising children, and in recent times, they have been engaged themselves professionally. Objectives: To compare insights into working and non-working women's mental and physical health. Methods: The study was conducted to perform a retrospective and comparative analysis of the sociodemographic status and health of working along with non-working women, as well as their kids. The study included both working and non-working mothers aged 25 to 45 who had their independent incomes. Their children were between 2 and 18 years old. The health factors being studied were bone density, body mass index, haemoglobin, calcium levels, and socioeconomic status (based on Kuppuswamy's scale). Data were analyzed by SPSS version 25.0. Results: The bone scan results of working and nonworking women differ significantly (p-value=0.033), indicating that working women had a little higher prevalence of osteopenia and hypocalcemia than nonworking women. However, the haemoglobin, body mass index, and socioeconomic status levels of both groups and their kids do not differ significantly. Conclusions: It was concluded that the comparison was made from the health outcomes of non-working and working women. Although some divergence and convergence were present, there is not much of a difference between health and sociodemographic characteristics.